Fatigue Indices and Perceived Exertion Highlight Ergometer Specificity for Repeated Sprint Ability Testing - Kerhervé, Hugo A.; Stewart, David G.; McLellan, Chris; Lovell, Dale (Frontiers in Sports and Active Living, 2020)
This study aimed to compare the time course of measures of performance, fatigue, and perceived exertion during repeated-sprint ability (RSA) testing performed on a non-motorized treadmill (NMT) and cycling ergometer (CE). Fourteen physically active participants performed two 10 ×6 s−1 RSA tests with a 1:4 work-to-rest ratio (24 s recovery) on NMT and CE. Measures of performance [peak and mean power output (PPO and MPO), cadence, and the time to reach PPO (TTP)] and of fatigue (fatigue index and decrement score) and ratings of perceived exertion (RPE) were collected during each session. The level of significance was set at p < 0.05. Participants completed the RSA test at a MPO of 1,041 ± 141 W on CE and 431 ± 48 W on NMT, achieving PPO of 2,310 ± 339 W on CE and 1,763 ± 289 W on NMT. Participants' weight was significantly correlated with PPO and MPO on CE (p < 0.001) and with MPO on NMT (p < 0.001). PPO on CE and NMT was significantly correlated only for absolute measures of power (p < 0.01). Cadence was higher and decreased throughout the RSA on NMT compared to CE, where it decreased only at the seventh bout. TTP was significantly shorter and more affected by fatigue on NMT than on CE. Fatigue indices were significantly greater on NMT compared to CE, with significant correlations between the decrement score and absolute and relative PPO on CE and NMT, between the fatigue index and absolute and relative PPO only on NMT, and no significant correlations with MPO. During RSA, RPE increased more on NMT compared to CE from bouts 3 to 7. During recovery, RPE was consistently higher on NMT at 1, 3, and 5 min post exercise compared to CE. These findings indicate that RSA performed on NMT induces greater fatigue and physiological load than CE, which originated in the lower resistive torque typically used on NMT compared to CE, resulting in a front loaded power output profile from the greater acceleration and cadence. From these results, we discuss that despite providing highly correlated measures of power output, NMT and CE should not be used interchangeably to assess RSA as they elicit markedly different responses. We also discuss these results from the fundamental differences in active muscle mass and power application patterns between running and cycling, which could form the basis of future studies.